Measurement and Control of Joint Interaction Torque for a Lower Limb Exoskeleton - Gonzalez-Mejia, Sergey; Ramirez-Scarpetta, Jose Miguel (IEEE ... Colombian Conference on Automatic Control (Online), 2023)
This paper details a theoretical analysis proposal for the measurement of the joint interaction torque in a lower limb exoskeleton, as well as the development of an assistance controller based on interaction torque rejection. The theoretical analysis is based on the principle of mechanical strain measurement using strain gauges, since there are a variety of measurement configurations using gauges but the requirements of the application must be taken into account. Therefore, a mathematical analysis of the mechanical model for the selected configuration is carried out in order to achieve the desired requirements, such as compensation of the temperature effects according to the type of material of the exoskeleton structure, and rejection of the effects of mechanical deformations in the structure due to tension-compression along movement in the sagittal and transverse planes because only bending moments are taken into account. A mathematical method based on Hooke's Law is also explained to obtain a direct measurement of the interaction torque in units of Newton-metro. The computation of human torque is derived from interaction torque, and motor torques. A control scheme for interaction torque rejection is deployed within Exo-H3 exoskeleton, where the experimental results with two healthy subjects show a good performance achieved by the controller.